Park Street looking towards Beacon Street in winter, ca. 1860-90 - Soule, John P. (Tufts Archival Research Center, 2005)
Street-level view northwest of Park Street looking towards Beacon Street. The dome and facade of the Massachusetts State House, which is located on Beacon Street, is visible along the center-right side of the carte-de-visite. The Boston Common, which is separated from the southwest side of Park Street by a wrought-iron fence, is included in left-half of the photograph. Street-lights line the northeast side of Park Street. Snow blankets the ground, trees and buildings included in the photograph. Two pedestrians stand on both sidewalks lining Park Street. 2 15/16 x 2 1/4, 3 15/16 x 2 7/16 overall Cartes-de-visite